Intervention Based Exclusively on Stage-Matched Printed Educational Materials Regarding Healthy Eating Does Not Result in Changes to Adolescents’ Dietary Behavior - Natacha Toral; Betzabeth Slater (The Scientific World Journal)
Purpose. To assess the impact of a six-month stage-based intervention on fruit and vegetable intake, regarding perceived benefits and barriers, and self-efficacy among adolescents. Design. Randomized treatment-control, pre-post design. Subjects/Setting. Schools were randomized between control and experimental groups. 860 adolescents from ten public schools in Brasília, Federal District, Brazil were evaluated at baseline; 771 (81%) completed the study. Intervention. Experimental group received monthly magazines and newsletters aimed at promotion of healthy eating. Measures. Self-reported fruit and vegetable intake, stages of change, self-efficacy and decisional balance scores were evaluated at baseline and post-intervention in both groups. Analysis. The effectiveness of the intervention was evaluated using the analysis of covariance model (ANCOVA) and repeated measurement analysis by means of weighted least squares. Comparison between the proportions of adolescents who advanced through the stages during the intervention was performed using the Mantel-Haenszel chi-square test. Results. After adjusting for sex and age, study variables showed no modifications through the proposed intervention. There was no statistical difference in participant mobility in the intervention and control groups between the stages of change, throughout the study. Conclusion. A nutritional intervention based exclusively on distribution of stage-matched printed educational materials was insufficient to change adolescents’ dietary behavior.